Morbidity profile of patients seeking care in private Siddha facilities in Tamil Nadu: a cross-sectional study - Samsthithaa; Sendhilkumar M; Sindhu R; Rajalakshmi K; Sivaraman G (International Journal Of Community Medicine And Public Health, 2026)
Background: The Siddha system of medicine is one of the widely practiced traditional medical systems in South India. Despite increasing utilization of Siddha services in both public and private sectors, evidence on morbidity patterns in private Siddha healthcare facilities is limited. This study aimed to describe the morbidity profile of patients attending Arogya Healthcare Private Limited in Chennai in 2024. Methods: We conducted a cross-sectional study using outpatient data collected from January to December 2024 from Arogya healthcare private limited clinics, Tamil Nadu. We extracted patient information, including age, sex, and clinical diagnoses, from the Electronic Health Record (EHR) system using a structured data extraction form. We analyzed the data using Epi Info software and present the findings as frequencies and proportions. Results: We extracted and analyzed 28,049 outpatient data. The majority of patients were female (57.1 %), and belonged to the 31-45-year age group (31%). The most frequently reported conditions were diabetes (12.5%), ulcers (7.4 %), osteoarthritis (7.4%), cold/cough (5.8%) and sinusitis (4.8%). Diabetes was at top in both sexes, but it varied in the following diseases. According to Siddha classification, vali-related disorders (40%) were more commonly reported. Conclusions: This study describes the morbidity pattern in private Siddha clinic. Many patients sought care were female, came for follow-up and chronic conditions like diabetes, ulcers, and osteoarthritis. The identification of pattern helps in the integration of data for the surveillance and developing standardized preventive and management strategies to reduce disease burden and improve quality of life.